Using Formative Evaluation Research in the Development of Electronic Media Programmes - D.P. VAN VUUREN; J .J. de Beer (Communicare)
TELEVISION producers have specific demands when asked about the types of insight they would like to gain from media research. In this paper an overview of the literature on "pilot programme testing" is given, and the technique of formative evaluation research on educational television is discussed. The latter technique was adapted for programme research on entertainment program ming in South Africa to address the specific needs of television and radio producers. Using three different methodologies, including measur ing audience reaction second by second, and "focus group" discussions, valuable insight In audience response have been gained. The results of this research suggest immediate practical implementation thereof, bringing the media researcher and media practitioner closer together. Dr D.P. van Vuuren is Head: Broadcasting Research at the SABC and Dr J.J. de Beer is Head: Media Effects Research of the Institute for Communication Research of the HSRC. The article was presented at the ninth Conference of the South African Marketing Research Association, Vanderbijlpark, November 1987.